2001
DOI: 10.1083/jcb.152.6.1169
|View full text |Cite
|
Sign up to set email alerts
|

A Role for Syndecan-1 in Coupling Fascin Spike Formation by Thrombospondin-1

Abstract: An important role of cell matrix adhesion receptors is to mediate transmembrane coupling between extracellular matrix attachment, actin reorganization, and cell spreading. Thrombospondin (TSP)-1 is a modulatory component of matrix expressed during development, immune response, or wound repair. Cell adhesion to TSP-1 involves formation of biochemically distinct matrix contacts based on stable fascin spikes. The cell surface adhesion receptors required have not been identified. We report here that antibody clust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
70
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(73 citation statements)
references
References 78 publications
(108 reference statements)
3
70
0
Order By: Relevance
“…Several extracellular matrix proteins, including fibronectin, collagen, thrombospondin, laminin, and tenascin, interact with cell surface proteoglycans and are thought to modulate cell adhesion through this interaction (2,21,33,45,50,82). In the present study, we have shown that vitronectin also supports proteoglycan dependent cell adhesion.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…Several extracellular matrix proteins, including fibronectin, collagen, thrombospondin, laminin, and tenascin, interact with cell surface proteoglycans and are thought to modulate cell adhesion through this interaction (2,21,33,45,50,82). In the present study, we have shown that vitronectin also supports proteoglycan dependent cell adhesion.…”
Section: Discussionsupporting
confidence: 55%
“…Primers (2) and (3) included a silent mutation (underlined = codon; boldface = base change) which created a unique Agel restriction site designed to facilitate the identification and selection of mutant vitronectin DNA containing this deletion. PCR reactions were performed which contained either primers (1) and (3) or primers (2) and (4), together with rVn in pRc/CMV (Invitrogen, Carlsbad, CA) as a template source. The PCR reactant products were combined in a second reaction to generate a single 613 bp recombinant mutant vitronectin fragment of DNA incorporating both the deletion mutation and the histidine tag, which were verified by DNA sequencing.…”
Section: Generation and Expression Of Recombinant Vitronectinsmentioning
confidence: 99%
See 1 more Smart Citation
“…The requirement for Sdc has been established for vertebrates, showing that the HSPG acts as an independent signaling receptor and has a number of functional features assigned to its cytoplasmic and extracellular domains, respectively. Its cytoplasmic domain functions in intracellular signal transduction and plays a role in the maintenance of epithelial integrity by linking the ECM to the actin cytoskeleton (9)(10)(11)(12). Furthermore, the transmembrane domain of Sdc not only serves to localize Sdc at the cell membrane but to mediate proteinprotein interactions (13).…”
mentioning
confidence: 99%
“…Fascin, which is expressed in normal mesenchymal, endothelial, dendritic, and neuronal cells but not in normal epithelia (Kureishy et al, 2002) is important in cell -cell interactions and adhesion (Adams et al, 2001), both interacting with specific tight (Wong et al, 1999) and adherens junctions (Tao et al, 1996) and intervening in focal adhesions via b1-integrin (Jawhari et al, 2003). Moreover, the protein promotes cell locomotion (Yamashiro et al, 1998) and participates in the mechanical organisation of stress fibres (Adams, 1997).…”
mentioning
confidence: 99%